Tacit attitudinal principles for evaluating digital preservation success - Abrams, Stephen (Archival science, 2021)
Digital preservation fulfills a critical role in the digital continuity of individual, institutional, and cultural memory. It is important for archival stewards and stakeholders to know whether or not those activities have been successful in order to deploy finite programmatic resources most relevantly, effectively, and productively. While preservation trustworthiness has been subject to extensive examination, the complementary evaluative quality of success has received less critical consideration. This study looks at how the preservation community ascribes meaning to the concept of success through attitudinal norms tacitly embedded in domain discourse. These are recovered through qualitative content analysis of selected preservation policy statements, which act as public affirmations of the archival service “contract” regarding stewardship intention and reciprocal stakeholder expectation. Success is a measure of the alignment between anticipated outcomes and actual preserved state resulting from intentional intervention. Communicological critique of the norms illuminates why the measure of success remains problematic and suggests avenues by which metrical practice can be augmented to enhance its evaluative power. This includes repositioning evaluative prerogatives to incorporate concern for the persistence not only of authentic digital information objects but also legitimate communicative experiences.